Contributions of an Extension Course Focused on Good Software Engineering Practices for Students and IT Professionals - Cavalcante, Victória Karolina de Lima; Costa, Catarina de Souza; Sarkis, Laura Costa; Soares, Daricélio Moreira; Freitas, Saulo Maia de (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2023)
In undergraduate courses in computing, there are criticisms about Software Engineering disciplines being too theoretical and about the difficulty of applying knowledge in real projects. Initiatives such as the WebAcademy project, which is a training course – based through active learning methodologies such as Problem-Based Learning and hands on – that qualifies participants to work in all stages of software development, can help prepare students for professional work. In this direction, this research investigated the perception of graduates of the WebAcademy project regarding their knowledge in SE before joining the course and after, in order to verify if the course contributed to the learning of concepts and practices (using the Project-Based Learning) that permeate the area. For this, a Survey was carried out with the graduates of the two classes of the project. As a result, it was verified that the students understood more about the importance of following good practices in software projects and developed more practical skills when working on the development of real projects.